Pemikiran Ekonomi Abu Yusuf - Fitri Hayati; Elvira Andriyani; Muhammad Iqbal; Popi Dea Ananda; Salsabila Sofiya Wardani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research uses a descriptive qualitative method aimed at examining technological-based innovations in Islamic Religious Education (IRE) learning media in the digital era. The study focuses on how technology is utilized to create interactive, creative, and relevant learning experiences for today’s students. In the age of digital transformation, IRE teachers are expected to provide learning that is not only textual and conventional but also contextual by incorporating technology such as educational videos, mobile applications, online learning pjlatforms, and social media. The data in this study were collected through a literature review of various scientific journals, academic articles, and recent research reports. The findings show that innovation in technology-based media can increase learning motivation, strengthen the understanding of Islamic values, and provide a more enjoyable and meaningful learning experience. Furthermore, the use of digital media supports the development of student character through adaptive and personalized approaches. Therefore, technological innovation in IRE learning media is a vital strategy in creating effective and competitive religious education.